Examining the nucleation mechanism of calcium oxalate nanoparticles, with and without surfactants, and assessing the influence of surfactants on nanoparticle size - Milad Hejazifar; Mehrdad Manteghian; Seyed Pezhman Shirmardi (Results in Chemistry)
This article describes the reactive crystallization method used for nanoparticle production. It emphasizes the significance of determining and controlling the nucleation mechanism by measuring induction time and solution supersaturation. Classical nucleation theory (CNT) was applied to identify the nucleation mechanism. Two surfactants, CTAB (Cetyltrimethylammonium bromide) and SDS (Sodium dodecyl sulfate), were utilized to prevent nanoparticle agglomeration. The presence of CTAB decreased the induction time (14 s), whereas SDS increased it (41 s). Nanoparticle measurements were conducted using Dynamic Light Scattering (DLS) analysis. Calcium oxalate nanoparticles formed through a homogeneous primary nucleation mechanism, unaffected by the type of surfactant. However, SDS resulted in smaller particles (under 100 nm) with a more uniform size distribution compared to CTAB.